Continuing education and self-perception of competence: a study with tennis coaches - Cortela, Caio Corrêa (2019)
This study aimed to relate the continuing education of coaches and self-perception with the importance attributed to the construct of professional competence. The sample included 69 tennis coaches participating in professional training sessions promoted by the Paraná Tennis Federation, who have more than eight years of professional experience, as well as ample experience as tennis players, and a university degree in Physical Education. A chart with sociodemographic variables and the Self-Perceived Competence Scale was used to collect data. Results indicated that participation in workshops/courses showed no significant relationship with the coaches self-perceived competences for the Professional Knowledge dimension. For the Professional Skills dimension, training was significantly related to self-perceived mastery, particularly on skills related to Sports Management and Planning and Sports Assessment, which are skills considered to be crucial in the professional lives of coaches. The importance given to Knowledge and Professional Skills was not only high but was always higher than the self-perception of the domain.